Juvenile polyposis syndrome: An unusual case report of anemia and gastrointestinal bleeding in young infant. Issue 37 (September 2016) - Hsiao, Yi-Han; Wei, Chin-Hung; Chang, Szu-Wen; Chang, Lung; Fu, Yu-Wei; Lee, Hung-Chang; Liu, Hsuan-Liang; Yeung, Chun-Yan
Abstract: Background: Juvenile polyposis syndrome, a rare disorder in children, is characterized with multiple hamartomatous polyps in alimentary tract. A variety of manifestations include bleeding, intussusception, or polyp prolapse. In this study, we present an 8-month-old male infant of juvenile polyposis syndrome initially presenting with chronic anemia. To the best of our knowledge, this is the youngest case reported in the literature. Methods: We report a rare case of an 8-month-old male infant who presented with chronic anemia and gastrointestinal bleeding initially. Panendoscopy and abdominal computed tomography showed multiple polyposis throughout the entire alimentary tract leading to intussusception. Technetium-99m-labeled red blood cell (RBC) bleeding scan revealed the possibility of gastrointestinal tract bleeding in the jejunum. Histopathological examination on biopsy samples showed Peutz-Jeghers syndrome was excluded, whereas the diagnosis of juvenile polyposis syndrome was established. Results: Enteroscopic polypectomy is the mainstay of the treatment. However, polyps recurred and occupied the majority of the gastrointestinal tract in 6 months. Supportive management was given. The patient expired for severe sepsis at the age of 18 months. Conclusion: Juvenile polyposis syndrome is an inherited disease, so it is not possible to prevent it. Concerning of its poor outcome and high mortality rate, it is important that we should increase awareness and education of the parents at its earliest stages.